Do Monetary Policy Outcomes Promote Stability in Fragile Settings? - Diallo, Oumar (IMF Working Papers; Working Paper ;, 2022)
This paper assesses how monetary policy outcomes affect fragility. Diving into the universe of the most prominent combinations of pursued monetary policy objectives across fragile settings, we examine the relationships between monetary policy outcomes and fragility and find the combination of reduction of inflation and lower unemployment to be the one that delivers the highest payoff in terms of promoting peace and cohesion. Setting aside challenges of monetary policy transmission, results from our analysis broadly confirm the above "winning" combination, with low inflation as a primary desired outcome and low unemployment rate as a secondary one. We also carry out a series of robustness tests, which confirm our findings. Overall, our results lend credence to the importance of paying attention-in the context of reducing fragility-to monetary policy outcomes.